Biomechanics' determinants of the trunk front semi-circular kick (Dollyo Chagi) in tae-kwon-do - Saeed Zahran, A.; Abdel-Moneim ElSeoufy, A. (World Journal of Sport Sciences, 2010)
Biomechanics' determinants of the trunk front semi-circular kick (Dollyo Chagi) in Tae-Kwon-do Represents the logical analysis of motor vehicle by which the subject of the study dealing with the phenomenon after the fragmentation of the primary elements to achieve a deeper understanding of the phenomenon as a whole. Taekwondo is a Martial Arts Olympics, can the player according to new 2009 amendments to the law in favor of ending the game in case the performance of three to four kicks during the match in just any tour as a special circular front kick (Dollyo Chagi), which ranked first in the skills the most commonly used in games, used to kick in each of the trunk and face of the player. The researchers noted the importance of that skill and importance of studying various aspects of technical,mechanical,prompting researchers to try to study the properties of the curve front kick circular (Dollyo Chagi) in the sport of Taekwondo. - The equity of the total time of performing the skills was in favor of the right and left where it reached (0.76 s.) - The amounts of the longest horizontal displacement of the kicking metatarsus was by 1.505m for the right foot kick and 1.477m to the left foot kick, with a difference of 0.028m represents a percentage of 1.86% which is . The amounts of the longest vertical displacement was by 1.597 m while the left foot kick achieved a vertical displacement of 1.531 m, with a difference of 0.066 m which is a very small difference that indicates the extent of accuracy when performing the skill with the two feet and represents a difference ratio of 4.13%. - The highest rates of total speed of the difference between the obtained speed with a percentage of 4.05%. C The largest rate of the kicking foot ankle's angular change ranged between (171.743°) to (160.038°) with a difference of (11.7°) with a ratio of (6.8%) which is a high percentage refers to the need of studying the causes of the differences between the two kicks of both feet. - The largest rate of the kicking foot knee joint's angular change during the performance ranged between (179.73°: 178.201°) with a difference of (1.52°) with a ratio of 0.84%, which is an excellent rate for achieving the further and higher horizontal and vertical distance of the kicking foot. - The largest rate of the hip joint's angular change ranged between (147.2°) to the right foot kick and (151.08°) to the left foot kick at (0.56 s.) with a difference of (3.12°) with a percentage of 2.06% - The kicking foot pushing amounts ranged between 8.825n/s. for right foot pushing and 10.662 n/s. for left foot pushing with a different of 1.83 n/m. represents a percentage of 17.22%.